Optimalisasi Layanan M-Paspor Sebagai Inovasi E-Government Dalam Meningkatkan Efektivitas Pelayanan Keimigrasian di Kantor Imigrasi Kelas I TPI Denpasar - Darmaputra, Kadek Indra; Prabawati, Ni Putu Anik (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to assess the effectiveness and optimization of the M-Passport service as an innovation within the e-government framework aimed at improving the quality of immigration services at the Denpasar Class I Immigration Office. In today’s digital age, developments in information technology are driving the transformation of public services toward greater speed, transparency, and efficiency, including in the field of immigration. The increase in the volume of passport applicants at the Denpasar Immigration Office has become a challenge that requires digital-based service innovations to support faster and more accountable administrative processes. The methods used include a qualitative approach with in-depth interviews, field observations, and documentation studies of the service systems and processes. The research results show that the implementation of digitalization through the M-Paspor application has significantly improved the efficiency of administrative processes, reduced waiting times, and strengthened the transparency and accountability of services. The obstacles encountered include daily quota limitations, technical system disruptions, and a lack of public understanding of how to use the application. As a solution, plans are in place to construct a new building and increase outreach activities to support the sustainability of services. The conclusion of this study confirms that the M-Paspor digital service innovation has had a positive impact on improving the quality of immigration services; however, continuous optimization and increased human resource capacity are needed to ensure more responsive, reliable, and inclusive services.